Improving the microstructure and tensile properties of AZ91 magnesium alloy via electromagnetic stirring. (7th February 2020) - Bian, Jiancong; Yu, Baoyi; Sun, Wanting; Jiang, Lei; Liu, Xingjun; Zheng, Li; Li, Runxia
Abstract: In this study, the effects of electromagnetic stirring on the microstructure and tensile properties of AZ91 magnesium alloy were investigated by XRD, SEM, TEM, EBSD and tensile test. The results show that the yield strength, ultimate tensile strength and elongation increase to 167 MPa, 187 MPa and 7.5%, rising by 35.8%, 43.8% and 114.3% after the electromagnetic stirring, owing to the refinements of α -Mg and β -Mg17 Al12 grains, the increased amount of low angle grain boundaries and the formation of a few tensile twins. The grain refinement mainly originates from the increase in nucleation rate. Electromagnetic stirring improves the plasticity of AZ91 alloy with poor ductility, and further increases the application of AZ91 alloy.